Report on a computer-controlled automatic test platform for precision RF cavity characterizations - Chen, Xiangcheng; Sanjari, Mohammad Shahab; Piotrowski, Jeremi; Hülsmann, Peter; Litvinov, Yuri A.; Nolden, Fritz; Steck, M.; Stöhlker, Thomas (Physica scripta, 2015)
An automated test platform aiming at accurate and efficient cavity characterizations has recently been set up at GSI, Darmstadt. In this proceeding the composition of such a system, on both hardware and software sides, is described in detail. The amount of necessary human work is significantly reduced to the minimum, while the measurement precision is improved considerably.